Shakespeare's companies William Shakespeare's early career and the acting companies, 1577 - 1594 - Schoone-Jongen, Terence (Studies in performance and early modern drama, 2008)
Focusing on the often neglected 1580s and 1590s, this study considers the plausibility of various biographers' claims about Shakespeare's involvement with different London acting companies. It considers 11 different acting companies, with six chapters on their activities, & the arguments for Shakespeare's involvement in them.